2022
DOI: 10.1002/msc.1647
|View full text |Cite
|
Sign up to set email alerts
|

The effects of adding splint use to corticosteroid injection for the treatment of trigger finger: A randomized controlled trial

Abstract: Background Trigger finger is the most common flexor tendinopathy affecting the general population. We evaluated the effects of adding a static metacarpophalangeal joint splint to corticosteroid injection for the management of trigger finger in the short term. Methods We carried out a randomized controlled trial with two parallel arms in Department of Physical Medicine and Rehabilitation at a university hospital. We randomly allocated 60 participants (34 women) with trigger fingers other than the thumb to two g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
1
1
Order By: Relevance
“…The splint-added group had greater reduction in pain (as measured by the Numeric Rating Scale for pain) and symptom severity (according to the Persian-translated Boston Carpal Tunnel Syndrome Questionnaire) at 3 months. There was no difference in reduction in functional scores between the groups [35]. Pain reduction at 3 months in the splint-added group of that study differs from our study, which found no differences in VAS score reduction between the steroid injection and combination treatment groups.…”
Section: Primary Outcomes: Pain and Functioncontrasting
confidence: 91%
See 1 more Smart Citation
“…The splint-added group had greater reduction in pain (as measured by the Numeric Rating Scale for pain) and symptom severity (according to the Persian-translated Boston Carpal Tunnel Syndrome Questionnaire) at 3 months. There was no difference in reduction in functional scores between the groups [35]. Pain reduction at 3 months in the splint-added group of that study differs from our study, which found no differences in VAS score reduction between the steroid injection and combination treatment groups.…”
Section: Primary Outcomes: Pain and Functioncontrasting
confidence: 91%
“…Pain reduction at 3 months in the splint-added group of that study differs from our study, which found no differences in VAS score reduction between the steroid injection and combination treatment groups. The difference might have been because of less-severe trigger finger presentations; for example, they excluded patients with underlying diabetes mellitus, a factor strongly associated with failure of local corticosteroid injection [4,15] and the prolonged splint protocol (full-time for 3 months) in the previous study [35]. Additionally, that previous study used the Boston Carpal Tunnel Syndrome Questionnaire to evaluate pain and function.…”
Section: Primary Outcomes: Pain and Functionmentioning
confidence: 99%